Penggunaan Nanosilika Pada Campuran Aspal Berpori Dalam Meningkatkan Kinerja Campuran - Muhammad Gunawan Perdana; Pratikso; Mudiyono, Rachmat (Universitas Veteran Bangun Nusantara, 2025)
The use of nanosilica in porous asphalt mixtures has become a major concern in research to improve the performance of asphalt mixtures. Nanosilica has the potential to improve the mechanical and rheological properties of mixtures, increase resistance to permanent death, and improve permeability and structural stability. This study was carried out using a literature reflection method (literature review) of relevant previous research to understand the impact of nanosilica on porous asphalt mixtures. This research aims to determine the effectiveness of nanosilica in increasing mechanical resistance, damage, and resistance to extreme environmental conditions. The results of the literature review show that the addition of nanosilica at levels of 2% to 6% can increase resistance to decay and permanent freezing. In addition, nanosilica also contributes to increasing the complex shear modulus, reducing Cantabro loss, and improving the connectivity of air voids in porous asphalt mixtures. Thus, nanosilica can be a promising additive in porous asphalt mixtures to improve structural durability and long-term performance. Further studies are needed to determine the optimal formulation to achieve a balance between stability, interference, and permeability. Keywords: nanosilica, porous asphalt, mixture performance, mechanical resistance, permeability.